2006
DOI: 10.1057/palgrave.jt.5740191
|View full text |Cite
|
Sign up to set email alerts
|

Using the decomposed theory of planning behavioural to analyse consumer behavioural intention towards mobile text message coupons

Abstract: Technology. Her research areas include business management, consumer behaviour and service management. AbstractThe rapid development and expansion of the global mobile phone market have made mobile phones another vital marketing communication channel, next to electronic and print media. Sending discount coupons through mobile phone text messages or short message service (m-coupons) has become the latest sales promotion trend for companies. As such, the factors influencing attitude and behavioural intention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…Even though there are considerable researches on mobile services, but there are not many studies on mobile coupons. With a few notable exceptions (e.g., Hsu, Wang, and Wen, 2006;Dickinger and Kleijnen, 2008), little research has been devoted to explore the factors that contribute to consumers' willingness to adopt mobile couponing. Little is still known about consumers' attitudes toward adopting, or not adopting, and factors that influence consumers' attitudes and value perceptions about them.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are considerable researches on mobile services, but there are not many studies on mobile coupons. With a few notable exceptions (e.g., Hsu, Wang, and Wen, 2006;Dickinger and Kleijnen, 2008), little research has been devoted to explore the factors that contribute to consumers' willingness to adopt mobile couponing. Little is still known about consumers' attitudes toward adopting, or not adopting, and factors that influence consumers' attitudes and value perceptions about them.…”
Section: Introductionmentioning
confidence: 99%
“…Research in environmental development has examined how texting assists Bangladeshi villagers to locate clean water sources (Opar 2006). Texting research extends to business and commercial uses (e.g., Bamba and Barnes 2007;Hsu, Wang, and Wen 2006;Mahatanankoon 2007), political campaigning (Prete 2007), and media broadcasting (Enli 2007). Closer to human communication research, psychologists have looked at compulsive texting (Rutland, Sheets, and Young 2007) and so-called cyberbullying (e.g., Raskauskas and Stoltz 2007;Smith et al 2008).…”
mentioning
confidence: 99%
“…Belch and Belch (2003) suggested that common classifi cations of promotional tools or activities can be divided into consumer-centered promotional activities and intermediate seller-centered promotional activities [2]. When vendors seek an immediate market response, they generally use price promotions to provide economic incentives that attract consumers [3,4]. However, when consumers deal with price information, there are many factors that will aff ect their fi nal decisions, such as the product prices faced in previous consumption experiences; when they later face new price information disclosed by the companies, they will have divergent responses.…”
Section: Promotional Activitiesmentioning
confidence: 99%